Fostering Communicative Competence Through Simple Project-Based Learning Approaches - Rangkun Wari Gunawan; Muhammad Husnu; Ahmad Yusri; Zahratul Fikni (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study investigated the effectiveness of Project-Based Learning (PBL) in enhancing the speaking skills of students at SMAN 1 Sembalun. Using a pre-experimental design with pre-test and post-test assessments, the research involved 16 eleventh-grade students. The results indicated a significant improvement in speaking abilities, with the average pre-test score of 48.75 increasing to an average post-test score of 71.56 after the PBL intervention. This shift reflected enhanced pronunciation, fluency, and grammar usage, demonstrating that students became more confident communicators. While PBL proved beneficial, challenges such as time constraints and the need for effective facilitation were identified. This research contributed to the growing body of evidence supporting PBL as an effective pedagogical approach, highlighting its potential to foster independent learning and improve communication skills.